The Effectiveness of Virtual Reality Sangiran Museum to Increase the Interest in Learning History of Class X High School Students - Vionita Vara Fitrianti; Risky Setiawan; Agung Bahroni (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Learning interest is a critical factor in determining the success of students' learning. Learning interest can be defined as students' attention and liking for a subject matter, characterized by a strong desire to learn and explore the material. This study aims to measure the effectiveness of learning media Virtual Reality Sangiran Museum in increasing students' interest in learning history. This study uses an experimental method with the One Group Pre-test Post-test Design model involving the same subject, namely 50 class X MA Sunan Pandanaran Yogyakarta students. The instrument used in this research is a questionnaire on students' interest in learning history. The results showed a significant difference in students' interest in learning history before and after using the learning media Virtual Reality Sangiran Museum. The results of the T-Test test showed a significance value of 0.000 <0.050, which can be concluded that there is an influence in the use of learning media Virtual Reality Sangiran Museum on students' learning interest. Meanwhile, based on the N-Gain test, the average g score is 0.720, which can be assumed to mean that the learning media of the Virtual Reality Sangiran Museum has an impact with high criteria on increasing students' interest in learning. This study concludes that using learning media, such as the Virtual Reality Sangiran Museum, in learning history effectively increases students' interest in learning history.